Design Considerations for a Portable Raman Probe Spectrometer for Field Forensics. (13th September 2012) - Kelly, James F.; Blake, Thomas A.; Bernacki, Bruce E.; Johnson, Timothy J.
Abstract : Raman spectroscopy has been shown to be a viable method for explosives detection. Currently most forensic Raman systems are either large, powerful instruments for laboratory experiments or handheld instruments for in situ point detection. We have chosen to examine the performance of certain benchtop Raman probe systems with the goal of developing an inexpensive, portable system that could be used to operate in a field forensics laboratory to examine explosives-related residues or samples. To this end, a rugged, low distortion line imaging dispersive Raman spectrograph was configured to work at 830 nm laser excitation and was used to determine whether the composition of thin films of plastic explosives or small (e.g., ≤10  μ m) particles of RDX or other explosives or oxidizers can be detected, identified, and quantified in the field. With 300 mW excitation energy, concentrations of RDX and PETN can be detected and reconstructed in the case of thin Semtex smears, but further work is needed to push detection limits of areal dosages to the ~1  μ g/cm 2 level. We describe the performance of several probe/spectrograph combinations and show preliminary data for particle detection, calibration and detection linearity for mixed compounds, and so forth.